A rapid method for the separation of the phospholipids from the neutral lipids in plasma. (June 2020) - Liu, Ge; Gibson, Robert
Highlights: This study reports a system capable of selectively separating plasma phospholipids from other lipid classes in just a few minutes. The new method produces almost identical results to conventional methods involving liquid/liquid extraction and thin layer chromatography separation. The new technique is a rapid and reliable method for the assessment of plasma phospholipid fatty acid composition. Abstract: The blood fraction most commonly used for the assessment of fatty acid status is the plasma or serum phospholipids, since these provide a measure of long term dietary intake. However, conventional assays of fatty acid status in human plasma and serum require labour intensive, multi-step approaches, which are impractical for high-throughput analyses. This study reports a system capable of selectively separating plasma phospholipids from other lipid classes in just a few minutes. We demonstrate that compositional analysis of the fatty acids in plasma phospholipids using our plasma spot method resulted in greater than 97% of neutral lipid standards had been eluted from the paper, whereas more than 96% of the PC remained on the paper. These results were almost identical to conventional methods involving liquid/liquid extraction and thin layer chromatography separation. Evaluation of our plasma spot fractionation and assay using plasma from 110 human subjects (75 males, 35 females), provides confirmation of significant correlations between the fatty acid measures and those obtained from conventional measures for all fatty acids ( r > 0.97, P <0.0001), including the omega (n)-6 ( r  = 0.988, P <0.0001) and n-3 long chain polyunsaturated fatty acids ( r  = 0.997, P <0.0001). These results establish our newly developed plasma spot separation technique as a rapid and reliable method for the assessment of plasma phospholipid fatty acid composition.